The Influence of Integrity on Employee Performance: Case Study from Provincial BAWASLU Secretariat West Sulawesi, Indonesia - Musdalifah, M.; Arsyad, Muhammad; Hajjad, Mu'fidatul Nurul (Manunggal Halim Jaya, 2024)
This research design is quantitative research, which aims to determine the influence of integrity on the performance of employees at the Bawaslu Secretariat of West Sulawesi Province. The General Election Supervisory Body (Bawaslu) is an election supervision institution that was formed to supervise the stages of election administration, receive public complaints, and handle cases of administrative election violations as well as criminal violations of elections based on the level of statutory regulations in Bawaslu which are regulated in Law No.7 of 2017 concerning General Elections. This research uses a simple linear regression analysis and data collection method through questionnaires. The t-test results showed that the calculated t-value for the integrity variable was 2.424, more significant than the t-table value of 2.034. The significance value was 0.021, which was smaller than 0.05, so integrity had a positive and significant effect on the performance of employees at the Bawaslu Secretariat of West Sulawesi Province. Meanwhile, the correlation coefficient analysis results showed that the correlation coefficient (r) was 0.389. This means that there is a positive correlation between the integrity variable (X) and employee performance (Y) with a weak level of relationship, and this correlation is significant because Sig 0.021 <0.05. Thus, integrity correlates with employee performance at the West Sulawesi Province Bawaslu Secretariat.